1991
DOI: 10.1073/pnas.88.6.2481
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of the genes for platelet-derived growth factor B-chain receptor and macrophage colony-stimulating factor 1 receptor during monocytic differentiation.

Abstract: Receptors for platelet-derived growth factor (PDGF) have not been identified previously to our knowledge in human myeloid cells that also produce PDGF. Here we report that phorbol ester-treated myeloid cells differentiated along the monocytic lineage express both a full-length 5.5-kilobase (kb) mRNA and a predominant, truncated 4.6-kb mRNA coding for the PDGF B-chain receptor (PDGF-BR). PDGF-BR was identified in phorbol ester-differentiated myeloid cells by indirect immunofluorescence with an antibody specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Several observations suggest that PDGFRβ signaling could play a role in hematopoietic cell proliferation. First, low level expression of PDGFRβ has been observed in murine myeloblastic, mast and multipotential cell lines (de Parseval et al ., 1993) and during the differentiation of primary monocytes and of cell lines THP1 and HL60 (Pantazis et al ., 1991; Inaba et al ., 1993). Second, PDGF treatment in several of these situations has been shown to induce a mitogenic response in both immature and mature cells (de Parseval et al ., 1993; Inaba et al ., 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Several observations suggest that PDGFRβ signaling could play a role in hematopoietic cell proliferation. First, low level expression of PDGFRβ has been observed in murine myeloblastic, mast and multipotential cell lines (de Parseval et al ., 1993) and during the differentiation of primary monocytes and of cell lines THP1 and HL60 (Pantazis et al ., 1991; Inaba et al ., 1993). Second, PDGF treatment in several of these situations has been shown to induce a mitogenic response in both immature and mature cells (de Parseval et al ., 1993; Inaba et al ., 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The PDGF competitor for the blots probed with Anti-A was PDGF-AA; for the blots probed with anti-PDGF, PDGF-AB was the competitor. isolated human blood monocytes, Pantazis et al (38) reported expression and production of PDGFR-13 in phorbol estertreated monocytic leukemia cell lines. Perhaps foreign body activation of macrophages induces expression of PDGFR-13 in a similar manner as phorbol ester.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of PDGFRa is specifically detected in subtypes of mesenchymal precursor cells located in the lung, skin, and intestine, whereas PDGFRb is expressed in pericytes and vascular smooth muscle cells (36). Other cells expressing PDGFRa are human platelets, mouse megakaryocytes, and rat liver endothelial cells (52)(53)(54); PDGFRb is expressed in mouse capillary endothelial cells (55), T cells, and macrophages (35,(56)(57)(58). Cultured monocytes (59) and natural killer (NK) cells (60) also express PDGFRb.…”
Section: Pdgf Receptorsmentioning
confidence: 99%